Number of Tape Twists Effects on Solar Water Heater Performance - J. Hasan, Iesam; Abdullah, Zaynab Ismail (International Journal of Integrated Engineering, 2023)
In solar applications, research into appropriate methods to improve the performance of the solar water heater is important. The current work studies improved the performance of the solar water heater by analyzing the effect of the number of added tape twists. A four-pipe solar water heater was built, and four twisted tapes were used, each with a different number of twists (flat, one, three, and five twists), and each tape was inserted into a pipe. The addition of twisted tapes has found that improved the performance of the solar water heater, and this improvement increased with the number of twists. A one, three, and five-twisted tapes achieved a temperature increase of (5.33, 14.09, and 20.27%) respectively, relative to a flat tape, and the instantaneous efficiency of the five twists tape was the highest, where the highest instantaneous efficiency of the four types rates (9.6, 13.4, 13.8, and 15 %) respectively.